Prognostic Usefulness of Systolic Blood Pressure One-Year Following Cardiac Resynchronization Therapy (from MADIT-CRT) - Abdulla, Khaled H.; Sherazi, Saadia; Goldenberg, Ilan; Kutyifa, Valentina; Zareba, Wojciech; Huang, David T.; Rosero, Spencer Z.; Polonsky, Bronislava; McNitt, Scott; Aktas, Mehmet K. (The American journal of cardiology, 2020)
Low systolic blood pressure (SBP) is associated with increased mortality and heart failure in patients with left ventricular dysfunction. Data on the relation between SBP measured following cardiac resynchronization therapy implantation and subsequent clinical events are limited. We hypothesized that assessment of systolic blood pressure at 12 months after cardiac resynchronization therapy can be used to identify patients with increased risk for adverse cardiovascular outcomes. The study population comprised 1000 patients who underwent cardiac resynchronization therapy implantation in MADIT-CRT. Outcomes were compared between patients with low (<110 mm Hg) and preserved SBP (≥110 mm Hg) at 1 year. At 1 year following cardiac resynchronization therapy, 800 patients (80%) had preserved systolic blood pressure. Kaplan-Meier survival analysis showed that the rate of heart failure or death during subsequent follow-up was significantly higher among patients with low SBP as compared with a preserved SBP at 12 months (2-year rates: 20% vs 12%, respectively; log-rank p value = 0.009 for the overall difference during follow-up). Consistently, multivariate analysis showed that patients with preserved SBP at 1 year had a 29% lower risk of HF or death when compared with the low SBP group (p = 0.024). The association between SBP measured following cardiac resynchronization therapy implantation and subsequent clinical events was more pronounced among patients with nonischemic cardiomyopathy (p value for SBP-by-HF etiology interaction = 0.034). In conclusion, assessment of SBP following cardiac resynchronization therapy can be used for improved long-term risk stratification in this population.